PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN YANG DIMEDIASI KEPUASAN KERJA - Ikhsan, Muhammad Deny; Supartha, I Wayan Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.09.TAHUN.2023DO - 10.24843/EEB.2023.v12.i09.p15, 2023)
Employee performance is the result of work that can be achieved by employees based on their abilities. So that employees can improve their performance. Companies need to pay attention to the factors that affect employee performance, namely work motivation and job satisfaction. The purpose of this study was to determine the role of job satisfaction in mediating the effect of work motivation on employee performance at PT. Omiyage Inc. Indonesia Dore By LeTAO Jakarta. This study used a sample of 83 employees, using probability sampling technique. The analytical technique used in this research ispath analysisand Sobel test. Collecting data through interviews and distributing questionnaires. The results of the study found that work motivation has a positive and significant effect on employee performance. Work motivation has a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on employee performance. Job satisfaction mediates work motivation on employee performance. High work motivation will increase job satisfaction so that it can improve employee performance